Respiratory inductance plethysmography: calibration techniques, their validation and the effects of posture. - Stradling, JR; Chadwick, G; Quirk, C; Phillips, T (1985)
Respiratory inductance plethysmography (RIP) is used to measure ventilation from two measurements of body surface movements (rib-cage and abdomen) via the application of volume-motion (V-M) coefficients. The correct derivation of both V-M coefficients (calibration) is necessary because there are considerable spontaneous variations in relative contributions from these two compartments even during resting breathing. In order to fully test a calibration, deliberate changes in rib-cage (RC) to abdominal (AB) contribution must be made. We used this approach to test two single-posture calibration techniques, multiple linear regression (MLR) and isovolume (ISV). Ten normal subjects and nine patients with chronic airway obstruction (CAWO) were studied using quiet breathing throughout. We also studied the effects of changing posture on the constancy of the V-M coefficients. MLR proved a little more accurate (p = 0.03) in deriving the V-M coefficients than ISV in normal subjects, and ISV consistently underestimated the AB V-M coefficient relative to RC. No difference between the two techniques existed in patients with CAWO. Both MLR and ISV calibrations failed to give acceptable calibrations in some patients. When MLR calibration was used, a deliberate 20% change in relative compartmental contribution (RC-AB) induced mean errors in RIP estimations of tidal volume of 3.5 and 9.5% in normal subjects and patients respectively. When there were no deliberate changes in relative contribution, the 95% confidence limits of individual tidal volume estimates were +/- 6.6 and +/- 12% in normal subjects and patients respectively. MLR calibration provides a statistical estimate of its quality at the time of V-M coefficient derivation.(ABSTRACT TRUNCATED AT 250 WORDS)